UNDERSTANDING EXTERNAL RELATIONS OF FEDERATED UNITS AND REGIONS - Sajic, Nina (Politeia, 2020)
This paper examines in detail the major themes that have emerged in the academic study of external relations of sub-state entities. It begins by exploring definitions of the external relations and international activities of federated units and regions and presents a brief history of when and how sub-state units emerged at the international scene; in other words, it considers the groundwork for their international presence and displays how changes in international relations create room for new actors. The paper then considers why federated units and regions engage in external relations, including their motivations, incentives, and strategies. The paper also examines the role of nationalism and separatism in the international activities of federated units and regions, how central authorities react, and what measures they may take against their sub-state units. The participation of regions and federated units in international organisations is also analysed here.
Keywords: Paradiplomacy; Diplomacy; Substate actors; Federalism; Federated units; Regions; International relations; Diplomatic tools; Nationalism; Separatism; International organisations